Tradition und Moderne in Kolumbien Das Neben- und Gegeneinander lyrischer Strömungen in den 20er Jahren - Pöppel, Hubert (Vervuert Verlagsgesellschaft, 1994)
Estudio sobre la poesía colombiana de los años veinte
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: Geschichte 1920-1930; Hispanic Literature, general; Literary Studies; LITERARY CRITICISM / American / General; Lyrik; Rezeption; Kolumbien; Hochschulschrift